UJI PROKSIMAT PELLET KAYU LAMTORO (Leucena leucocepalla) LOKAL SUMBAWA SEBAGAI BAHAN BAKAR ALTERNATIF - Azis, Abdul; Aldrin; Nanda, Nanang Dwi (Wakil Rektor 3, Direktorat Riset, Publikasi dan Inovasi, Universitas Teknologi Sumbawa, 2025)
The availability of national oil and natural gas fuel reserves shows a downward trend, and is even predicted to run out in the next 9 years for petroleum products and 19.9 years for natural gas. Meanwhile, national demand for oil and gas continues to increase along with population growth. This causes an energy crisis which has an impact on the national economic crisis. So, strategic steps are needed to diversify new and renewable fuel sources originating from community-based managed biomass. On Sumbawa Island, the availability of lamtoro trees is abundant and available throughout the year and has not been utilized, except for goat feed. Lamtoro is an invasive plant species that can disrupt ecosystems, but its functions and economic benefits are rarely explored. Energy from lamtoro wood biomass has a calorific value according to SNI 8021:2014 standards so it is suitable as a substitute for fossil fuels to achieve energy security in the future. The aim of this research is to make wood pellets from an invasive plant species, namely lamtoro, by obtaining data, including proximate test data. This research method is experimental, namely the proximate test. The proximate test consists of testing water content, ash content, volatile matter content, bound carbon and heating value. Proximate testing results for wood pellets based on SNI 8021:2014 Wood Pellets. The results of this research include: maximum calorific value of 4211 cal/g (sample 5), lowest ash content of 0.66 (sample 5), lowest water content of 8.01 (sample 5) lowest volatile matter content of 60.72% (sample 5), the highest bound carbon content was 15.65% (sample 5). From the results of this research, Lamtoro wood pellets have met SNI 8021:2014 standards.